Orodispersible lozenges containing a combination of Lactobacillus reuteri DSM 17938 and Lactobacillus reuteri ATCC PTA 5289 and normal gum function: evaluation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 - EFSA Panel on Nutrition, Novel foods and Food Allergens (NDA); Dominique Turck; Jacqueline Castenmiller; Stefaan De Henauw; Karen Ildico Hirsch‐Ernst; John Kearney; Helle Katrine Knutsen; Alexandre Maciuk; Inge Mangelsdorf; Harry J McArdle; Androniki Naska; Carmen Pelaez; et al. (EFSA Journal, 2020)
Abstract Following an application from BioGaia AB submitted for authorisation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of Sweden, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to orodispersible lozenges containing a combination of Lactobacillus reuteri DSM 17938 and Lactobacillus reuteri ATCC PTA 5289 and normal gum function. The scope of the application was proposed to fall under a health claim based on newly developed scientific evidence. The Panel considers that orodispersible lozenges containing L. reuteri DSM 17938 and L. reuteri ATCC PTA 5289 are sufficiently characterised. Maintenance of normal gum function is a beneficial physiological effect. Out of the two studies from which conclusions could be drawn and that investigated the effect of lozenges containing L. reuteri at the proposed conditions of use (i.e. consumption twice daily) on appropriate gingival outcomes (bleeding on probing (PoB) and gingival index (GI)) in subjects with gingivitis, but without periodontitis, one showed a large effect on BoP and other gingival outcomes and one showed no effect. No effect was found in one study with the use of one lozenge daily. The three studies that investigated, at the proposed conditions of use, modified GI (and not BoP or GI) in subjects with gingivitis, but without periodontitis, or were conducted in patients with periodontitis support an effect of lozenges with L. reuteri on gum function. Some evidence has been provided for mechanisms by which consumption of lozenges containing L. reuteri could improve outcomes of gingivitis in patients with chronic periodontitis but the relevance of such mechanisms for the target population of the claim (i.e. subjects without periodontitis) is unclear. The Panel concludes that the evidence provided is insufficient to establish a cause and effect relationship between the consumption of orodispersible lozenges containing a combination of L. reuteri DSM 17938 and L. reuteri ATCC PTA 5289 and maintenance of normal gum function.